Does the Non-Financial Factor Affect the Profitability of Islamic Commercial Banks - Tsania Ardhya Pratama; Segaf Segaf (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
The growth of the Islamic Finance Industry shows positive developments. The average growth of these assets is around 0.12% annually, allowing the Islamic banking industry to optimize profits and limit risk to as small as possible. This study wants to reveal whether or not there is an influence of non-financial factors, namely intellectual capital and Islamic social reporting, on profitability. The population includes Islamic Commercial Banks in Indonesia and uses the purposive sampling technique, so there are 12 types of Islamic Commercial Banks. This research used secondary data using the annual report from their website for the period 2016 to 2020. Found that the probability value of intellectual capital was 0.9901 or more than alpha (0.05), so that partially intellectual capital did not affect the profitability. Another factor is Islamic Social Reporting which has a probability value of 0.0070 or less than alpha (0.05), so Islamic Social Reporting partially affects the profitability. Based on the simultaneous test, the Prob value (F-statistic) is 0.000003 or less than alpha (0.05), so the Intellectual Capital and Islamic Social Reporting variables simultaneously affect the profitability of Islamic Commercial Banks.